Seasonal Microbial Community Characteristic and Its Driving Factors in a Copper Tailings Dam in the Chinese Loess Plateau - Jia, Tong; Guo, Tingyan; Yao, Yushan; Wang, Ruihong; Chai, Baofeng (Frontiers in Microbiology, 2020)
A combined soil bacterial and fungal community survey was conducted for a copper tailings dam in the Chinese Loess Plateau. We investigated the seasonal differences in the composition and function of soil microbial community to examine the key environmental factors influencing soil microorganisms during restorative ecological processes. Significant seasonal differences were found in the community structure of both bacterial and fungal communities. Bacterial community abundance and fungal community (Shannon index) measurements were highest in summer. Soil nitrite nitrogen (NO2−-N) was the dominant factor influencing both bacterial and fungal communities. The bacterial community composition was significantly affected by NO2−-N and ammonia nitrogen (NH4+-N) in spring, and fungal community structure was significantly affected by soil water content in autumn. Moreover, the fungal community exhibited significant functional feature differences among seasons, whereas bacterial community functional groups remained similar. This study aimed to clarify the adaptation response of microbes applying different approaches used in ecological restoration approaches specific to mining areas, and to identify the natural biofertility capacity of the microbial communities that colonize soil ecosystems.